Solubility of aceclofenac in polyamidoamine dendrimer solutions - Patel, Jaydeep; Garala, Kevin; Basu, Biswajit; Raval, Mihir; Dharamsi, Abhay (International Journal of Pharmaceutical Investigation)
In the present study we investigated the effect of polyamidoamine (PAMAM) dendrimers on the aqueous solubility of aceclofenac. The aqueous solubility of aceclofenac was measured in the presence of dendrimers in distilled water. The effect of variables, such as pH condition, concentration, temperature and generation (molecule size) of dendrimer, has been investigated. Results showed that the solubility of aceclofenac in the dendrimer solutions was proportional to dendrimer concentration. The order in which the dendrimers increased the solubility at a constant pH condition was G3 > G0. The influence of dendrimer solution pH on the solubility enhancement of aceclofenac suggests that it involves an electrostatic interaction between the carboxyl group of the aceclofenac molecule and the amine groups of the dendrimer molecule. The solubility of aceclofenac was inversely proportional to the temperature of dendrimer solution.Different generation (G0 and G3) PAMAM dendrimers have the potential to significantly enhance the solubility of poor water-soluble drugs.
Keywords: Aceclofenac; dendrimer; polyamidoamine dendrimers; solubility enhancement